ANXIETY SYMPTOMS IN PATIENTS WITH CONVERSION DISORDER - Akhtar, Javaid; Shah, Ulfat; Zaman, Safeer (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the frequency of anxiety symptoms in patients with Conversion Disorder. Methodology: This cross sectional study was conducted in Department of Psychiatry, Khalifa Gul Nawaz Hospital Bannu from August 2014 - March 2015. Sixty consecutive indoor patients of conversion disorder, diagnosed on the basis of ICD-10 criteria were assessed in detail. A semi-structured interviewwas conducted for demographic details. Results: Among Sixty indoor patients, 52 (86.6%) were females, thirty six (66%) unmarried and more than 80% (n=50) were uneducated. Similarly, about 89%(n=54) belonged to the age range between 10 and 30 years. Large majority(n=56, 93.3%) were residing in the rural areas. All patients (100%) reportedsomatic anxiety symptoms along with clinical presentation of conversion disorder. Most common symptoms reported were feelings of being light andweak (n=59, 98.3%), followed by palpitation (n=58, 96.6%). Conclusion: Patients with conversion disorder need to be assessed in detail for somatic anxiety symptoms in order to improve upon intervention strategies in this common psychiatric disorder.